O desacordo em uma reunião de trabalho: funções discursivas - Fernandes, Lindinalva Zagoto (2011)
Disagreement in oral interaction has been studied by researchers from several fields of knowledge and in different contexts. Some investigate its occurrence in casual conversation, others are concerned about disagreement in institutional talk. In Brazil, the existing studies are restricted to analyses of the organizational structure of disagreement and its position in the conversation. However, to my knowledege, except for Pertaki´s research (2005), no other proposal has dealt with examining the role played by discourse disagreement within communicative purpose. The disagreement study in daily conversations has been associated with the conversation analysis research (POMERANTZ 1984), as well as the Politeness Theory (BROWN and LEVINSON 1987). Both approaches show differences between them, but there are convergent points between them: both accept the fact that conversational exchanges strive to maintain and increase the complicity among the participants involved. However, this objective seems to happen in the conversation-among-peers data, but not in other contexts. On the other hand, the extent of face threat or dispreference involved therein is, indubitably, connected to the demands of the situational and cultural contexts of the speech event in which the act occurs (BLUM-KULKA 1997; REES-MILLER 2000). As a contribution to this study, this research examines 1043 conversational interlocutions that occurred in a meeting containing eight members of a real estate brokerage firm, in order to analyze the discourse function of the disagreement in the context of power institutionally. The study has the theoretical-methodological and interdisciplinary support formed by Conversation Analysis assumptions, Theory of Politeness (BROWN; LEVINSON, 1987), Critical Linguistics, (FOWLER et al., 1979) and Systemic Functional Linguistics (HALLIDAY, 1994; 2004). The analyses show complex sequences of disagreement made implicitly and explicitly, according to the legitimization of professional identity; the defense of personal interests and dissatisfaction with the working philosophy of the company